Resistance Mechanism Exhibited by Selected Maize Varieties to Asian Corn Borer Ostrinia furnacalis Guenee (Lepidoptera: Crambidae), Philippines - Karen B. Alviar; Gerald M. Duza; Chester Allan T. Mainem; Gerwin T. Alcalde (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2021)
Theresistance mechanisms exhibited by the five selected maize varieties against Ostrinia furnacalis [Gueene] or the Asian corn borer (ACB) were identified and evaluated in the study in terms of the insects’ percent mortality and development. The detached leaf-feeding assay was used in the experiment and laid out in Complete Randomized Design (CRD) with 5 treatments and replicated three times. Findings among the five selected maize varieties tested against ACB, Bt corn had exhibited a high degree of antibiosis mechanism. This was expected because of the Bt toxin from the maize variety conferring toxicity to Lepidopterous insect pests like ACB. A similar result with Variety 4 (Yellow Dent corn) was observed which shows a high degree of antibiosis mechanism that is innate within the maize leaves of the variety. Variety 1 (UPLB Lagkitan), Variety 2 (Yellow corn), and Variety 3 (White corn) show high susceptibility to ACB. Tolerance of the corn varieties to ACB needs to be further investigated because it is unknown to date whether the varieties possess or lack plant tolerance characteristics. Leaf whorl feeding assays used in the study only measure the antibiosis and antixenosis mechanisms in maize. Furthermore, a test to measure tolerance mechanisms is suggested among the maize varieties.